Discharge Summary: Reflections and Proposal for a Practical Guide - Barreto, Vasco (Portuguese Journal Internal Medicine, 2025)
A discharge summary is a clinical report relative to an episode of hospitalization. Its role is to ensure the transition of care between healthcare teams. Writing a discharge summary is a structured exercise of synthesizing relevant information, explaining the reasoning behind decisions and communicating the healthcare plan. A discharge summary is an opportunity to look at the patient´s situation as a whole and to update the priorities of their individual care plan. The Government determined a set of minimum mandatory information to normalize discharge summaries. This instrument is useful, but it does not replace the clinical report itself, which is a highly personalized document, impossible to parameterize. To ensure that a free field text is not structurally fragile, it is necessary to adopt a recording system that allows dealing with complex systems, such as problem-oriented medical records. In practical terms, a guide for writing problem-oriented discharge notes is proposed.<span class="EOP SCXW253759030 BCX0" data-ccp-props=""134233117":false,"134233118":false,"201341983":0,"335551550":6,"335551620":6,"335559685":0,"335559731":0,"335559737":0,"335559738":0,"335559739":160,"335559740":360">